Nutritional status of preschool children attending kindergartens in Kosovo - Agim Rysha (Journal of Health, Population and Nutrition, 2017)
Abstract Background There is very limited data on malnutrition of preschool children in Kosovo. The main objective of the study is to provide a nutritional status profile of preschool children attending kindergartens in Kosovo. Methods Cross-sectional study of children aged 12–59 months (n = 352 children) and children aged 60–83 months (n = 134) enrolled in public and private kindergartens of Kosovo. Anthropometric measurements used for this study are weight and height of the preschoolers (12–83 months). A measuring board was used for measuring the length/height of children younger than 2 years, while digital weight and height scale Seca 763 was used for measuring of preschool children taller than 110 and Seca 213 was used for measuring the height for children who were shorter than 110 cm. Statistical analyses of underweight and overweight trends across sex and age groups as well as between children from public and private kindergartens were carried out. Qualitative variables were tested with a chi-square test. The differences between groups were assessed with a Student t test for normally distributed variables and a Mann-Whitney test for abnormally distributed numerical variables. Results The mean z-scores for weight-for-age, height-for-age, weight-for-height, and BMI-for-age largely fell within 0.0 and 1.0. The percentage of stunted children is 3%, whereas child wasting is 1.9%. The overall percentage of obese children is 2.3%; furthermore, 8.9% are overweight and 27.3% have a possible risk of being overweight. Conclusions The incidence of children underweight is slightly decreasing. The prevalence of overweight and obese children in sample chosen is evident.